Penerapan Pendekatan Culturally Responsive Teaching (CRT) dengan mengintegrasikan Permainan Tradisional “Cungklik dan Boi” untuk Meningkatkan Hasil Belajar Peserta Didik Kelas V SDN 33 Mataram pada Mata Pelajaran Matematika - Spir Senyum Rekasawiji; Dadi Setiawadi; Sri Lestari (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study employed Classroom Action Research (CAR) aimed at improving students’ learning outcomes in Mathematics through the implementation of a Culturally Responsive Teaching (CRT) approach integrating the traditional games Cungklik and Boi. The research subjects consisted of 24 fifth-grade students at SDN 33 Mataram. The study was conducted in two cycles using the Kurt Lewin CAR model, which includes the stages of planning, action, observation, and reflection. Data were collected through observation and tests, including diagnostic tests and learning outcome assessments. The results showed that the application of the CRT approach through traditional games significantly improved students’ learning outcomes. In the pre-cycle stage, the level of learning mastery reached only 37.51% with an average score of 71. After the implementation in Cycle I, mastery increased to 79.16% with an average score of 83.79. In Cycle II, learning mastery further improved to 91.67% with an average score of 90.29. In addition to quantitative improvements, students’ active engagement, enthusiasm, and collaboration also increased throughout the learning process. These findings indicate that the CRT approach, which incorporates local cultural contexts into Mathematics learning, is effective in enhancing students’ learning outcomes and engagement.